Bio regulation of Meloidogyne incognita (Kofoid & White) Chitwood and M. javanica (Treub) Chitwood complex in coffee roots - Castro-Toro, Angela Maria; Rivillas-Osorio, Carlos Alberto (Revista de Ciencias Agrícolas, 2023)
The Meloidogyne incognita and M. javanica complex cause damage to the coffee plants’ roots with loss of productive potential. Traditional management against this complex is based on the use of chemical molecules which causes problems in soil health and harmful to the environment. In this regard, the Micosplag® biotechnological input [Paecilomyces lilacinus (Thom) Samson, 1974, Metarhizium anisopliae (Metsch) Sorokin and Beauveria bassiana (Balsamo) Vuillemin] and Tricho-D® (Trichoderma harzianum Rifai, 1969) were evaluated under greenhouse conditions against root-knot nematode complex. A dose of 2g. L-1 of water was used for Micosplag® and 10g. L-1 of water for Tricho-D®, applying a volume of 20mL.1 per plant. The nematode inoculation was carried out eight days after the sowing, using 2500 eggs per plant. Bioinputs were applied preventively and also as bioregulators of an existing nematodes population. Nine treatments, which corresponded to different moments of application of bioinputs in soil and soil plus vermocompost were evaluated. Results showed the lowest levels of infection when the Micosplag® bioinput was applied preventively (infection level of 6%), followed by the Tricho-D® treatment (infection 12%). There were statistical differences with the controls which were inoculated alone with the nematodes. When the two Bioinputs were applied preventively, they offered greater protection to the roots against nematodes. Dry weights of root and the aerial part of the plants showed the lowest values in treatments where the nematode was inoculated. Six months after the experiment was established, the three fungi that compose the Micosplag® Bioinput were isolated from the rhizosphere of the coffee plants.